1998
DOI: 10.1093/emboj/17.5.1259
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of primate immunodeficiency virus infectivity by Vif is cell species restricted: a role for Vif in determining virus host range and cross-species transmission

Abstract: The primate immunodeficiency virus Vif proteins are essential for replication in appropriate cultured cell systems and, presumably, for the establishment of productive infections in vivo. We describe experiments that define patterns of complementation between human and simian immunodeficiency virus (HIV and SIV) Vif proteins and address the determinants that underlie functional specificity. Using human cells as virus producers, it was found that the HIV-1 Vif protein could modulate the infectivity of HIV-1 its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 50 publications
(91 reference statements)
3
123
1
1
Order By: Relevance
“…This issue remains to be probed, but several species-specific restrictions have been discovered in the biology of lentiviruses. [19][20][21][22][23] Second, the genGene Therapy omic complexity of HIV is far greater than that of most other lentiviruses, including feline immunodeficiency virus and equine infectious anemia virus, which each have only six genes instead of the nine present in their human counterpart. Because in all cases a minimum of three genes, gag, pol and rev, will likely be required to generate vector particles efficiently, the multiply attenuated HIV-based packaging system will be the farthest removed from its parental virus.…”
Section: Current State Of the Art In Lentiviral Vector Design And Biomentioning
confidence: 99%
See 1 more Smart Citation
“…This issue remains to be probed, but several species-specific restrictions have been discovered in the biology of lentiviruses. [19][20][21][22][23] Second, the genGene Therapy omic complexity of HIV is far greater than that of most other lentiviruses, including feline immunodeficiency virus and equine infectious anemia virus, which each have only six genes instead of the nine present in their human counterpart. Because in all cases a minimum of three genes, gag, pol and rev, will likely be required to generate vector particles efficiently, the multiply attenuated HIV-based packaging system will be the farthest removed from its parental virus.…”
Section: Current State Of the Art In Lentiviral Vector Design And Biomentioning
confidence: 99%
“…The stereotactic injection of only a few microliters of vector preparation allows the transduction of tens to hundreds of thousands of neurons in the absence of any significant inflammatory or vectorspecific immune response. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] The expression of the foreign protein is long-lasting, at least for the transgenes that have been tested so far. While VSV G-pseudotyped particles target neurons almost exclusively, preliminary evidence indicates that other viral envelopes might permit the more efficient transduction of cells such as astrocytes.…”
Section: The Most Promising Applications Of Lentiviral Vectorsmentioning
confidence: 99%
“…Although Apo3G has the most potent anti-HIV-1 activity among the APOBEC family of proteins, another member of the family, APOBEC3F (Apo3F) was shown to inhibit HIV-1 infection in the absence of Vif (Bishop et al, 2004a;Liddament et al, 2004;Wiegand et al, 2004;Zheng et al, 2004), whereas APOBEC3B (Apo3B) can inhibit HIV-1 infection in both the presence and absence of Vif (Bishop et al, 2004a;Doehle et al, 2005;Rose et al, 2005). Although we can imagine the broad range of antiretroviral activity of APOBEC family because APOBEC proteins from non-human species can also inhibit HIV-1 infection (Bishop et al, 2004a;Bishop et al, 2004b;Cullen, 2006;Mariani et al, 2003;Wiegand et al, 2004), the Vif-Apo3G interaction is thought to be species specific (Mariani et al, 2003;Simon et al, 1998). Accordingly, hApo3G is insensitive to SIVagm Vif while african green monkey Apo3G (agmApo3G) is insensitive to HIV-1 Vif and the determinant of this species specificity depends on amino acid 128 of hApo3G and agmApo3G (Bogerd et al, 2004;Mangeat et al, 2004;Mariani et al, 2003;Schrofelbauer et al, 2004;Xu et al, 2004).…”
Section: Apobec: Enzymatic Restriction Factor That Target Retrovirusesmentioning
confidence: 99%
“…Previous studies suggested that the Vif protein of various primate lentiviruses typically functioned only in the host species from which the virus was derived (16), and the species-specific exclusion of Apobec3G in virions by Vif (17) accounted for this host specificity. That is, human Apobec3G was inhibited by Vif from HIV-1 but not by Vif from the SIV of AGMs (SIVagm), whereas AGM apobec3G was inhibited by Vif from SIVagm but not by Vif of HIV-1 ( Fig.…”
mentioning
confidence: 99%
“…Because SIVrcm is able to replicate in primary human cells, its Vif protein it likely to already have the capability to inactivate human Apobec3G. Additionally, the Vif protein of SIV from macaques (SIVmac, or SIVsmm in its original form) interacts with both macaque and human apobec3G (16,17), and there are even some strains of SIV isolated from a subspecies of African green monkeys that already replicate in primary human cells to some extent (22) and thus likely already encode a Vif protein that can inactivate human Apobec3G. Thus, we argue that the ability of an SIV to overcome the human antiviral defense, Apobec3G, is already present in the wild.…”
mentioning
confidence: 99%